Two episodes of Taravana syndrome in a breath‐hold diver with hyperhomocysteinemia. Issue 5 (8th March 2018) - Accurso, Giuseppe; Cortegiani, Andrea; Caruso, Sabrina; Danile, Oriana; Garbo, Domenico; iozzo, Pasquale; Vitale, Filippo; Raineri, Santi Maurizio; Gregoretti, Cesare; Giarratano, Antonino
Key Clinical Message: Taravana syndrome is a rare dysbaric disease characterized by neurologic signs and symptoms. Differently from others decompression illness, it has unspecified pathophysiology and unclear predisposing factors. Our cases suggest that thrombophilic state due to hyperhomocysteinemia could increase the risk to develop Taravana syndrome. Abstract : Taravana syndrome is a rare dysbaric disease characterized by neurologic signs and symptoms. Differently from others decompression illness, it has unspecified pathophysiology and unclear predisposing factors. Our cases suggest that thrombophilic state due to hyperhomocysteinemia could increase the risk to develop Taravana syndrome.